Tax Collection in the Tax Area of ​​Luang Prabang Province - Lathtanaphoubai, Bounthanom; Phomlasaboud , Khantavan; Somsacksaisompheng , Oulavieng (Souphanouvong University Journal Multidisciplinary Research and Development, 2026)
This research aims to study the tax collection in Luang Prabang Province over the last 5 years, from 2020 to 2024. The research collected the secondary data from the summary of the status of activities and implementation of tax collection in Luang Prabang Province, obtained from Luang Prabang Customs, International Airport Customs, 30 local customs checkpoints, and the Lao-China Railway Station Office. The data was divided into categories of goods for each type of tax collection. The data was obtained on annual revenues by comparing the tax collection of each region to compare the plan and actual implementation, including explaining the causes and reasons. The study found that: - The determination of tax collection each year was based on the potential and growth conditions of the domestic economy, including the global economic situation and, most importantly, the economic situation of that region, including the policies of the government to stimulate the economy. - The tax collection plan in 2020 was 14,769,070,000 kip, but can be implemented at 18,589,982,500 kip (125.87%); in 2021, it was 10,000,000,000 kip, but can be implemented at 8,030,872,300 kip (89.23%); in 2022, it was 10,000,000,000 kip, but can be implemented at 17,429,114,750 kip (172.49%); in 2023, it was 21,000,000,000 kip, but can be implemented at 61,805,557,500 kip (294.31%); and in 2024, it was 31,000,000,000 Kip, but can be implemented at 35,689,955,522.70 kip (113.66%). It can be seen that in 2023, the revenue collection exceeded the set plan, which was as high as 294.31%. In 2023, the highest tax collection was achieved, which was achieved from tax collection from 3 main sources: 1) vehicle fines, 2) vehicle fees, and 3) construction equipment taxes. Only in 2021, taxes could not be collected according to the rapid tax collection plan.